PENINGKATAN HASIL BELAJAR MELALUI MODEL E-LEARNING DENGAN MEDIA VIDEO PADA SISWA KELAS IX SMP NEGERI 1 CIKARANG BARAT - Sri Endah Harmonis (STIT Islamic Village Tangerang, 2021)
This research is an effort to improve IPA learning outcomes through e-learning models with video media in students of class IX SMPN 1 Cikarang Barat. This is because teachers only give assignments such as taking notes and reading does not guarantee students will study at home. The provision of assignments without the learning materials delivered by teachers to make IPA learning outcomes is still fairly low or still under KBM which is 75. This research uses Class Action Research in the form of the application of an e-learning model with video media to improve the learning outcomes of students of class IX SMPN 1 Cikarang Barat which consists of two cycles and each cycle consists of planning, implementation, observation, and reflection. Research subjects in students of class IX SMPN 1 Cikarang Barat. The 32 students consisted of 18 male students and 14 female students. The results showed that the application of e-learning models with video media can improve IPA learning outcomes in students of class IX SMPN 1 Cikarang Barat. Judging from the results of the student pre-cycle completed KBM only 14 students (43.75%), and 18 students (56.25%) have not been completed. In cycle I there was 27 students (84,375%) who were completed and 5 students (15,625%) who were not completed, and in cycle II there were 29 students (90.625%) who were completed and there were 3 students (9,375%) who were not completed. From the improvement of learning outcomes, this class action research was stopped in cycle II because it had achieved the classical completion criteria of ≥ 85% of the total number of students who completed learning and was declared successful to improve IPA learning outcomes in students of Class IX SMPN 1 Cikarang Barat Year of Study 2019/2020.